Tingkat Keberhasilan Program Peningkatan Fasilitas Ruang Terbuka Hijau (RTH) Terhadap Pemanfaatan Taman Kota di Kecamatan Kota Kabupaten Kudus - Hermawan, Aditya (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
The uncontrolable of development in the city has caused the green open area become rare. To fulfill it through Regent Private Constitution number 16 of 2012 and number 10 2013 The Government of Kudus has been trying to develop facilities of the Green Open Space in form of rehabilitation and development of the town park which scatter in a few districtsin Kudus Regency. The problem is that the program of development in Green Open Space is only review in the physical Development, not in the uses aspect. Those can be proved by the factual conditions on the field that showed of the neglection and started to break down in Krida Wisata Park and Ganesha Park. The research is using accesibility, comfortability, security, visiting reasons, frequent of time, and frequent ofÂ  visits, and the satisfaction of the visitors according to the available facilities there. According to Tangkilisan (2005) the use of town park can be rate effectives if there is satisfactory shown by the visitors. The visitors satisfaction about the facilities can be measured and concluded whether the program is success or not in the town park. Perceptions and preferences of the visitors can be a valuable addition to build up a dream town park that fits with the society. Eventually the analysis result has given image that the development of facilities program for Krida Wisata Park dan Taman Ganesha didnâ€™t run well, this can be caused by inapropriate and inadequates expectation in condition of facilities in town park. Most of the visitors expected to conduct any services to whole in both of Krida Wisata Park, especially in Ganesha Park. Society involvement as an important instrument in the construction must be maintain to escort the development process.